2011
DOI: 10.1055/s-0031-1272822
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Prolapse

Abstract: Rectal prolapse is a condition that usually requires surgical intervention to correct. Abdominal and perineal approaches are well described in the literature. Abdominal approaches have traditionally been reserved for young healthy patients, but this has been challenged by perineal approaches with excellent outcomes. Laparoscopic techniques have been shown to be effective and equivalent to traditional laparotomy techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 35 publications
0
46
2
3
Order By: Relevance
“…However, in these procedures, the decreased perioperative morbidity could be connected with the increased recurrence rate. There are three most commonly performed procedures: the perineal rectosigmoidectomy (Altemeier procedure), the perineal rectosigmoidectomy with levatoroplasty and the Delorme procedure [4,10]. In our study, actually we noted higher recurrence rates in overall perineal group of patients but we did not reveal any statistical significance.…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…However, in these procedures, the decreased perioperative morbidity could be connected with the increased recurrence rate. There are three most commonly performed procedures: the perineal rectosigmoidectomy (Altemeier procedure), the perineal rectosigmoidectomy with levatoroplasty and the Delorme procedure [4,10]. In our study, actually we noted higher recurrence rates in overall perineal group of patients but we did not reveal any statistical significance.…”
Section: Discussioncontrasting
confidence: 67%
“…In our series, all cases were electively operated on, and we used the Altemeier procedure in the majority of our recurrences with good results. The mortality rate after the elective procedure ranges from 0 to 5 % [10,21,25]. In our study, no mortality was reported in the Altemeier group.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations